KONTRIBUSI PEMIKIRAN HASBI ASH-SHIDDIEQY TENTANG HADIS DAIF - Ahmad Zuhri; Nurliana Damanik; Maulin Permata (UIN Sumatera Utara Medan, 2022)
Hasbi Ash-Shiddieqy is a scholar, expert on Jurisprudence, expert on Tafsir Al-Quran, Hadith expert and Indonesian academic. Hasbi Ash-Shiddieqy is also a figure who is an expert in the field of Hadith, he has many views in the field of Hadith as well as on Daif Hadith. In addition, he is a prolific scholar who has ideas about Islam. In line with the main research, this study aims to find out an explanation of the steps of the Daif Hadith according to Hasbi Ash-Shiddieqy, to find out the views of Hasbi Ash-Shiddieqy and the ulama in responding to the Daif Hadith. The research method of this thesis is a type of qualitative research, the source of the research is to collect data that has been found previously so that it can be understood easily by the author which is very necessary so that it can be known related to Hasbi Ash-Shiddieqy's Thoughts on Daif Hadith. This research is also classified as library research, where the author will utilize data sources in the form of literature related to the discussion. Based on the results of the research conducted, it shows that in determining the authenticity of the Hadith Hasbi has his own opinion regarding the conditions for the acceptance of the Hadith Sanad which can be said to be Sahih, namely Ittisal al-sanad (continuation of the sanad), Shadb (safe from oddities or not contrary to a more sophisticated history), Congratulations from illat, All narrators are fair, All narrators are Dhabit. If any of these conditions fail then the Hadith becomes Daif. Regarding Daif Hadith, Hasby As-Shiddieqy argues that all scholars do not agree to allow Daif Hadith to be used as evidence to establish a law. Daif Hadith can only be used as a charity for the practice of Sunnah. Here it is emphasized that there are different definitions of practice with fadhail charity. Practice is the thing that is recommended to be done while the fadhail of charity is the virtue or reward after doing a deed.